2002
DOI: 10.1159/000058381
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of 21-Hydroxylase and 11β-Hydroxylase Deficiency in Adrenal Incidentalomas and in Subclinical Cushing’s Syndrome

Abstract: Objective: The prevalence of steroid secretion abnormalities was studied by evaluating the 17-hydroxyprogesterone (17-OHP) and 11-deoxycortisol (S) responses to adrenocorticotropic hormone (ACTH) stimulation in 48 patients with ‘nonfunctioning’ incidentalomas and in 10 patients with ‘subclinical’ Cushing’s syndrome. Methods: In all patients the cortisol, 17-OHP, and S levels were measured after ACTH test. Eight patients were reinvestigated after surgery. Results: In patients with nonfunctioning lesions, the AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…[9][10][11][12][13] In our case reduced activity of 21-hydroxylase within the tumor (normal 17OHP levels after tumor excision) could account for the exaggerated response of 17OHP to ACTH, and the increased testosterone, and Ä 4Á levels. Similar overresponse of 17OHP to ACTH has been described before in ten patients with sub-clinical Cushings syndrome, 14 showing that alterations in enzymatic pathways can coexist with the presence of cortisol autonomy. Co-secretion of cortisol and androgens (elevated DHEAS, Ä 4Á , and testosterone) has also been described in six cases of adrenal tumors where there was no evidence of malignancy.…”
Section: Discussionsupporting
confidence: 81%
“…[9][10][11][12][13] In our case reduced activity of 21-hydroxylase within the tumor (normal 17OHP levels after tumor excision) could account for the exaggerated response of 17OHP to ACTH, and the increased testosterone, and Ä 4Á levels. Similar overresponse of 17OHP to ACTH has been described before in ten patients with sub-clinical Cushings syndrome, 14 showing that alterations in enzymatic pathways can coexist with the presence of cortisol autonomy. Co-secretion of cortisol and androgens (elevated DHEAS, Ä 4Á , and testosterone) has also been described in six cases of adrenal tumors where there was no evidence of malignancy.…”
Section: Discussionsupporting
confidence: 81%
“…However, this metaanalysis only included studies with 21OHD. Impaired 11β-hydroxylation activity has been demonstrated in functional adrenocortical tumors and non-functional adrenal incidentalomas based on in-vitro enzymatic analyses or ACTH stimulation test [158][159][160][161]. Bilateral giant adrenal incidentalomas have been reported in a 22-year-old man who after investigations turned out to have 11βOHD and the karyotype was 46XX [162].…”
Section: Adrenal Tumorsmentioning
confidence: 99%
“…Among the participants of that study, the 17-OH P levels declined to normal levels in seven of eight patients treated with surgery. In addition, the adrenal incidentaloma patients exhibited enzymatic diversity with alterations in enzymatic pathways being a phenomenon mostly associated with glucocorticoid autonomy (24). The results of that study showed that the possible effects of changes in steroideogenetic pathways on adrenocortical tumor formation can be documented using molecular analysis.…”
Section: Discussionmentioning
confidence: 89%
“…A decade ago, researchers suggested that adrenal tumors are capable of changing their enzymatic activity (24). Previously, 21-hydroxylase and 11 beta hydroxylase deficiencies were explored in a study consisting of 48 cases of adrenal incidentaloma and 10 cases of subclinical CS (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation